PENGARUH MAGNETIK Fe3O4 PADA SERBUK KARBON TERHADAP TINGKAT PENYERAPAN LIMBAH LOGAM Fe - Nur Akmal; Erman Taer; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The study on  synthesis  and  characterization  of magnetic   carbon from  mixture of rubber wood sawdust and    for  heavy metal  of Fe  absorption on the Siak river water samples  has been done.  The process of milling and seaving  resulted  a smallcarbon  particle size  of  38 μm, the increase in surface area of  the  carbon  has beenachieved  by  chemical activation using the KOH Activator  with  weight  ratio  of  carbonpowder  of  4: 1. After that,  carbon powder that had  been activated  was  mixed  to by  comparison of 5: 4. The mixing  process was  done  using  a  mortar and continued  toballmiling  process for 2 hours. Finally, a mixture of carbon powder and   was carbonized at  temperature  of   850oC    in  N2 gas and then proceed to  washing and drying proceses in order to produce carbon magnetic  . Absorption testing of heavy metal of Fe  in  Siak  river water samples  was  performed with variations in  immersing time of ½   hours, 1 hour,  and 2 hours. Atomic absorption spectroscopy test results revealed that absorption after 2 hours  increased from  34,17%  (without     to  39,63%  (using magnetic   .  Characterization  of x-ray diffraction  showed  the  peak  of  Fe  at  2θ = 46,28o and  scanning electron microscopy  showed  uniform  particle  size  with  irregular shape  and  whitish  color.  Results  of  Dispersive X-Ray  Energy (DXE) proved the existence of metal Fe in magnetic carbon absorbent material   from rubber wood sawdust.